Archival materials of A. V. Burdukov (Kalmyk national songs) - Ubushieva, Danara V. (The New Research of Tuva, 2013)
Article presents the structure of archival materials in the Archive funds of Kalmyk Institute for the Humanities of Russian Academy of Sciences which contains Kalmyk national songs written down by A.V. Burdukov in 1930’s.